The Role of AI Writing Assistance Tools in Supporting EFL Students’ Research Proposal Writing - Vivi Aulia (Jurnal Pendidikan Bahasa dan Sastra, 2026)
This research aims to investigate how AI writing assistance tools can support students in the research proposal writing process. It was conducted on 15 EFL undergraduate students at Universitas PGRI Kalimantan who composed their research proposals using these tools. The data were gathered through structured interviews and documentation focusing on students’ experience of using AI writing assistance tools for research proposal writing, its benefits, its drawbacks, and how the writing area improved after using the tools. This research revealed that during the research proposal writing, the majority of the students utilized these tools to help them generate ideas, create an outline, provide sample sentences, translate complex texts, and summarize the research paper articles. In addition, the findings also demonstrate that these tools help them improve their vocabulary, compose the background and literature review sections of their proposal, and correct the sentences properly. Furthermore, this research has also revealed some drawbacks of these tools. This research’s drawbacks from students’ experiences include oversimplified explanations obtained from the tools and their over-reliance on these tools. It can be concluded that AI writing assistance tools should be wisely utilized as a supplementary tool rather than a replacement tool for critical thinking and academic writing skills.